Revision of the Eurasian species of Aegilips Haliday, 1835 (Hymenoptera: Figitidae: Anacharitinae) - Mata-Casanova, Noel; Selfa, Jesús; Pujade-Villar, Juli (European Journal of Taxonomy, 2022)
The knowledge of Aegilips in Eurasia is updated. One new species is described: Aegilips insularis Mata-Casanova and Pujade-Villar sp. nov., from Portugal (Madeira). The genus is also cited for the first time in the Indomalayan region with specimens of A. atricornis found in Northern India and Pakistan. Aegilips curvipes Giraud, 1860, Aegilips gemellus Belizin, 1961, Aegilips laevis (Hedicke, 1914), Aegilips montanus Belizin, 1951 and Aegilips punctatus Belizin, 1951 are synonymized with A. nitidulus (Dalman, 1823). Aegilips vena Fergusson, 1985 is synonymized with Aegilips zaitzevi Kovalev, 1974. Aegilips notatus Belizin, 1951, and Aegilips punctulatus Hedicke, 1928 are designated as incertae sedis. The known distributions of A. atricornis, A. kozlovi, A. nitidulus and A. romseyensis are expanded. Morphological differences are discussed and a key for Eurasian Aegilips species is also given.